2020
DOI: 10.1371/journal.pone.0234539
|View full text |Cite
|
Sign up to set email alerts
|

Serum discrimination and phenotype assessment of coronary artery disease patents with and without type 2 diabetes prior to coronary artery bypass graft surgery

Abstract: Diabetes Mellitus (DM) accelerates coronary artery disease (CAD) and atherosclerosis, the causes of most heart attacks. The biomolecules involved in these interrelated disease processes are not well understood. This study analyzes biomolecules in the sera of patients with CAD, with and without type (T) 2DM, who are about to undergo coronary artery bypass graft (CABG) surgery. The goal is to develop methodology to help identify and monitor CAD patients with and without T2DM, in order to better understand these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…They found higher methylation at cg05825244 in EBF4 (among our 12 CpGs differentially methylated in VLBW adults), which was associated with a 23% increased risk of acute coronary syndromes. Further, mass spectrometry of sera from patients about to undergo coronary artery bypass graft (CABG) surgery identified that presence of EBF4 protein was more prevalent and helped distinguish patients with T2DM [ 67 ]. Our gene network analysis identified that in VLBW adults EBF4 is a key gene in a network centering on the serine/threonine protein kinase, Akt , which has key roles in many signaling pathways [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found higher methylation at cg05825244 in EBF4 (among our 12 CpGs differentially methylated in VLBW adults), which was associated with a 23% increased risk of acute coronary syndromes. Further, mass spectrometry of sera from patients about to undergo coronary artery bypass graft (CABG) surgery identified that presence of EBF4 protein was more prevalent and helped distinguish patients with T2DM [ 67 ]. Our gene network analysis identified that in VLBW adults EBF4 is a key gene in a network centering on the serine/threonine protein kinase, Akt , which has key roles in many signaling pathways [ 68 ].…”
Section: Discussionmentioning
confidence: 99%